United States : 2018 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
Unemployment is low, inflation is well contained, and growth is set to accelerate. During the course of this administration, the economy is expected to enter the longest expansion in recorded U.S. history.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet